Apply the Zero Power Rule to create an equivalent expression to 4/3(−2+1^0).(1 point)
An equivalent expression to 4/3(−2+1^0) is 4/3(−2+ ? ).
3 answers
An equivalent expression to 4/3(−2+1^0) is 4/3(-2+1).
Solve the expression 2(1.6^0+7)−4.9^0.(1 point)
2(1.6^0+7)−4.9^0=
.
2(1.6^0+7)−4.9^0=
.
First, we need to evaluate the exponent 0, which means any number raised to the power of 0 is equal to 1.
1.6^0 = 1 and 4.9^0 = 1
Now, we can substitute these values back into the expression and evaluate it.
2(1+7)-1 = 2(8)-1 = 16-1 = 15
Therefore, 2(1.6^0+7)−4.9^0 is equal to 15.
1.6^0 = 1 and 4.9^0 = 1
Now, we can substitute these values back into the expression and evaluate it.
2(1+7)-1 = 2(8)-1 = 16-1 = 15
Therefore, 2(1.6^0+7)−4.9^0 is equal to 15.